Revisited The Importance and Performance Analysis (IPA) and Kano Model for Customer Satisfaction Measurement - Sihombing, Haeryip; M.Y., Yuhazri; S.H., Yahaya; Z.A., Myia Yuzrina; A.Z., Ainul Azniza (Global Engineers and Technologists Review, 2012)
This study is to find out what the result of qualitative and quantitative approaches related to customer satisfaction if its measurement is carried out by integrating the measurement of customer satisfaction refers to the importance-performance (IPA) concept and Kano model into SERVQUAL attributes format. By considering the attributes aspects of SERVQUAL related to criteria of quality service with a case in education institution, the survey using questionnaires developed on the importance-satisfaction analysis (IPA) of 5 point of Likert scale were then performed in order to investigate the current of satisfaction condition. While the Kano criteria associated to the dichotomous statements contain of functional and dysfunctional of quality attributes level were then used to quantify the qualitative response. In this study, the domain of functional and dysfunctional of Kano is discussed and reviewed, including how their correlation against IPA and vice versa. By integrating of both approaches, the correlation between both will represent each of their characteristics as to be compared to each other, in which the result can be justified as the priorities of customer satisfaction. In addition, the consistencies of response data based on the approaches related to the criteria of KANO diagram against the functional and dysfunctional element can be defined in order to characterize the background and types of survey questionnaires